2011
DOI: 10.1039/c0py00238k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of anion conductive ionomers containing fluorenyl groups for alkaline fuel cell applications

Abstract: A series of anion conductive aromatic ionomers, poly(arylene ether)s containing different polymer backbones and quaternized ammonio-substituted fluorenyl groups, were synthesized via nucleophilic substitution polycondensation, chloromethylation, quaternization, and the subsequent ion exchange reactions. The ion exchange capacity (IEC) of the ionomers was controlled to be from 0.68 to 2.54 meq. g À1 by the chloromethylation reaction conditions. The designed chemical structures were wellcharacterized by the 1 H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 29 publications
2
97
0
Order By: Relevance
“…The decomposition temperature of the polymer backbone was similar to that of the parent polymer, 7 suggesting that the decomposition of the quaternary ammonium groups did not trigger degradation of the polymer backbone, which was observed in some aromatic AEMs. 50 As mentioned above, the degradation of PTMA functionalized 4 membranes occurs under high pH conditions probably via (i) Hoffmann elimination and (ii) direct nucleophilic substitution. 19,22,23 To further evaluate the stability and degradation mechanism of the 4 membranes, 4(X50) membrane with IEC of 1.32 mequiv/g was treated with 4 M NaOH aqueous for different exposure times.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The decomposition temperature of the polymer backbone was similar to that of the parent polymer, 7 suggesting that the decomposition of the quaternary ammonium groups did not trigger degradation of the polymer backbone, which was observed in some aromatic AEMs. 50 As mentioned above, the degradation of PTMA functionalized 4 membranes occurs under high pH conditions probably via (i) Hoffmann elimination and (ii) direct nucleophilic substitution. 19,22,23 To further evaluate the stability and degradation mechanism of the 4 membranes, 4(X50) membrane with IEC of 1.32 mequiv/g was treated with 4 M NaOH aqueous for different exposure times.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The final quaternization step keeps lowering the initial decomposition temperature to~190°C while maintaining the two-stage decomposition profile of brominated samples. The first stage can be attributed to the decomposition of the QA groups, while the second stage is the decomposition of the aromatic backbones [21,27]. The 5% weight-loss temperatures (T d-5% ) for QA-OMPFEK-20 and QA-TMPFEK-40 are 236.0°C and 250.6°C, respectively.…”
Section: Articlesmentioning
confidence: 99%
“…For chloromethylation route, the PAE precursors should contain electron-rich phenyl rings that are not connected to any electron-withdrawing group such as ketone or sulfone. Nevertheless, the chloromethylation requires the use of carcinogenic chloromethylation reactant (e.g., chloromethyl methyl ether), and the reaction degree is hard to control, with the risk of cross-linking [27]. These drawbacks hindered the employment of chloromethylation in the design and preparation of high performance AEMs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Friedel-Crafts chloromethylation reaction of this kind of polymer takes approximately one week and there are risks of cross-linking to become insoluble. [126][127][128] Tanaka et al recently synthesised a block poly (arylene ether)s anion exchange membrane with a excellent conductivity of 0.144 S cm À1 at 80 C. 127 The fuel cell performance using hydrazine and pure oxygen reached 297 mW cm À2 . Kim from Los Alamos National Laboratory reported that poly (phenylene) based AEM prepared by Sandia National Laboratory using aminated tetramethoxyphenylporphirine (TMPP) obtained good chemical and mechanical stability (stable >670 h at 60 C in 4 M NaOH), due to the wholly aromatic structure.…”
Section: Further Development Of Anion Exchange Membranes (Aems)mentioning
confidence: 99%